Modeling the Acoustic Channel of Voice Information Leakage - Олейников, А. М.; Білоцерківець, О. Г.; Shirokyi, O. (MC&FPGA, 2023)
The article analyses the modelling of an acoustic channel for voice information leakage. The model consists of 5 parts that are coordinated with each other by mathematical expressions. The results of experimental studies are presented. The proposed model can be used as a basis for software for modelling the acoustic channel of voice information leakage.
Keywords: modeling; channel; voice; information; leakage